Facility Layout Redesign Using Systematic Layout Planning: A Case Study of a Vocational Motorcycle Workshop in Indonesia - Yuanda, Rizwan; Fiatno, Aris; Gusman, Deddy; Tanjung, Lilatul Syifa; Musridho, R. Joko (Journal of Engineering Science and Technology Management, 2024)
Efficient facility layout plays a critical role in improving operational performance, learning effectiveness, and occupational comfort in vocational education workshops. This study examines the redesign of a motorcycle engineering and business workshop at a public vocational high school in Indonesia using the Systematic Layout Planning (SLP) method. The existing layout exhibited inefficient material flow, excessive travel distances, and poor spatial organization, leading to fatigue among students and reduced instructional productivity. A qualitative descriptive case-study approach was employed, supported by direct observation, process mapping, and activity relationship analysis. The SLP procedure was applied through the development of Operation Process Charts, Activity Relationship Charts (ARC), Activity Relationship Diagrams (ARD), and block layout alternatives. The proposed layout demonstrates a substantial reduction in inter-facility travel distance and improved logical sequencing of learning activities. The findings confirm that SLP is an effective and adaptable approach for optimizing educational workshop layouts, contributing to improved operational efficiency and a safer, more conducive learning environment.